A study on the influence of creative strategies in online advertising towards consumers’ attitude and purchase intention - Kwong, You Seng (Department of Media and Communication Studies, Faculty of Arts and Social Sciences, University of Malaya, Malaysia., 2017)
The purpose of this paper is to study the influence of creative strategies (humour, code-switching and visual communication) in online advertising on consumer’s attitude towards advertisements and purchase intention. Boundaries of culture and nonboundaries of brands, online platforms and niche consumer market limit the brand’s ability to be noticed and outstand, thus require effective creative strategies. Limited literatures discuss on effective creative strategies in online advertising. This study applied a factorial 2 x 3 design of experimental research, conducted on 120 UCSI University undergraduate students who were randomly selected and assigned to two different groups and sets of stimuli. The results of this study shows that the treatment group with three creative strategies has significantly better attitude towards the advertisement, and higher purchase intention compared to the non-treatment group. Code-switching was the most effective creative strategy, followed by visual communication and humour. The treatment group also shown to be more effective than the non-treatment group. Online advertising requires creative strategy elements to create favourable attitude and purchase behaviour among targeted consumers. This study has created practical implications to all advertisers, advertisements designers or business owners in advertising industries as this study helps to broaden their horizons in creativity aspect.